PDF Treatment of intraoral pyogenic granuloma with diode laser 810-980 nmarch - al-majeed, Aya; Aldelaimi , Tahrir N. (Iraqi Journal of Laser, 2022)
Background: Pyogenic granuloma is a hyperplastic benign tumor. The most common intra-oral site is marginal gingiva. It is often occurred in the second decade of life, it has a strong tendency to recur after simple excision.The aim of study: to evaluate the therapeutic advantages of diode laser (810-980 nm) in intraoral Pyogenic granuloma management.Materials and method: A total of 28 patients (14 men and 14 females) were enrolled in this study and had their pyogenic granuloma surgically removed using a diode laser. All of the patients were given local anesthetic and went through the identical surgical procedure (cartridge containing 1 percent lidocaine with epinephrine 1:100.000). To achieve hemostasis and minimize bleeding, the lesions were completely eliminated by sweeping the laser fiber tip across the operated site. To allow the wounds to heal, they were not sutured. Then, the specimens sent for histopathology.Results & Conclusions: In the present study, we noticed that the scale of pain, bleeding and oedema gradually decreased during the first two visits. the measured parameters were completely disappeared after two weeks in most cases as well as the patient satisfaction and function also improved. the Patients were recalled after two weeks, the wounds had completely healed and patients were not complaining any type of discomfort. it is generally believed that poor oral hygiene and poor fitting denture may lead to recurrence. According to obtained results; removal of pyogenic granuloma with diode laser (810-980 nm) is successful, effective and reasonable alternative to conventional scalpel technique.The aim of study: to evaluate the therapeutic advantages of QuickLase dentalase diode laser(810-980 nm) in intraoral Pyogenic granuloma management.Materials and method: A total of 28 patients (14 men and 14 females) were enrolled in this study and had their pyogenic granuloma surgically removed using a diode laser. All of the patients were given local anesthetic and went through the identical surgical procedure (cartridge containing 1 percent lidocaine with epinephrine 1:100.000). To achieve hemostasis and minimize bleeding, the lesions were completely eliminated by sweeping the laser fiber tip across the operated site. To allow the wounds to heal, they were not sutured. Then, the specimens sent for histopathology.Results & Conclusions: In the present study, We noticed that the scale of pain,bleeding and oedema gradually decreased during the first two visits. the measured parameters were completely disappeared after two weeks in most cases as well as the patient satisfaction and function also improved. the Patients were recalled after two weeks, the wounds had completely healed and patients were not complaining any type of discomfort. it is generally  believed that poor oral hygiene and poor fitting denture may lead to recurrence. According to obtained results; removal of pyogenic granuloma with QuickLase dentalase diode laser (810-980 nm) is successful ,effective and reasonable alternative to conventional scalpel technique.Keywords: pyogenic granuloma, QuickLase, benign hyperplasia, laser institution, Baghdad.